The higher degree research journey as a three-legged race - Dibble, Brian; Van Loon, Julienne (2004)
This paper focuses on the relationship between Higher Degree Research candidates and their supervisors within the Creative Writing discipline. The paper was prompted, in part, by discussions between the two authors during 2003 regarding the evaluation and selection of Creative Writing Higher Degree Research candidates at our own institution in preparation for the following academic year. One author is a Professor with more than twenty years experience in supervision, the other is a young academic with several years experience as an Associate Supervisor, more than half-way through her own doctoral degree in Creative Writing, and about to embark on the Principal Supervisor journey for the first time.